2018
DOI: 10.1111/bjet.12672
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ perception and engagement in Facebook learning groups

Abstract: This study presents and evaluates the educational potentials that Social Network Services (SNS) offer to students in the higher education context. The first aim of this study is to explore students’ perceptions of Facebook Learning Groups (ie, Facebook Groups that were created for learning purposes), and the learning and affective benefits that SNS offer to students. This study further explores the influence of four identified factors (ie, self‐efficacy, privacy, trust and presence of teaching members) in mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…This indicates that there are students with strong preferences for and against social learning. This is in line with the findings of Hong and Gardner (2019), who found that junior students prefer to interact on a social media platform while more mature students prefer the LMS. The results from Question 9 confirmed that privacy was not a major concern for most students (only 5 agreed and strongly agreed) when deciding to participate in a social learning group (Hong & Gardner, 2019).…”
Section: Social Engagementsupporting
confidence: 91%
See 3 more Smart Citations
“…This indicates that there are students with strong preferences for and against social learning. This is in line with the findings of Hong and Gardner (2019), who found that junior students prefer to interact on a social media platform while more mature students prefer the LMS. The results from Question 9 confirmed that privacy was not a major concern for most students (only 5 agreed and strongly agreed) when deciding to participate in a social learning group (Hong & Gardner, 2019).…”
Section: Social Engagementsupporting
confidence: 91%
“…To this effect, student views about engagement within the module were obtained through a questionnaire. The questions were based on literature and were adapted from the questionnaires of Hong and Gardner (2019) and Stanley and Zhang (2018). The questionnaire, which consisted of closed-and open-ended questions, was administered to the students through a Google Form link.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, as well as offering a wide range of topics in terms of entertainment, being a social media tool, it can be suggested that Facebook also keeps the potential for learning and gathering information from different fields and promotes collaborative learning (Menzies, Petrie & Zarb, 2017). This can be considered as a suggestion that Facebook can be used as a complementary tool (Hong & Gardner, 2019). This is also supported in other research which suggest that Facebook enables users to discuss on a subject that they are interested in by giving them an endless space and sharing opportunity which ultimately results in supporting students in their learning and can be used for educational activities (Luke, 2019;Ware, Kern, & Warschauer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%